Formation of Amomum subulatum Nano-Suspension and Evaluation of Angiotensin Converting Enzyme (ACE) Inhibition Potential: Formation of Amomum subulatum - Munazza Rashid; Nazish Jahan; Zill-e-Huma; Khalil-Ur-Rehman; Talha Zulfiqar (Biological Sciences - PJSIR, 2022)
Amomum subulatumis act as a excellent antihypertensive and its bioactives exhibited detox properties. Low bioavailability and solubility of bioactive compounds as a result of complex structure is the main problem of less therapeutic efficiency of medicinal plants. The main objective of this research was formulation of Amomum subulatum nanosuspension to enhance ACE inhibition potential. A. subulatum nanosuspension was prepared by anti-solvent precipitation method by using sodium lauryl sulphate stabilizer and optimized by Response Surface Methodology. The prepared nanosuspensions were characterized by zeta sizer and scanning electron microscopy. Nanosuspension with 136 nm particle size and 0.215 PDI value was optimized and selected for further in vitro study. The scanning electron microscopy showed spherical shaped nanoparticles with smooth topology which confirmed formulation of nanosuspension. Optimized nanosuspension showed better ACE inhibition potential of 80% as compared to crude extract (36%). Results of antimicrobial activity showed greater zone of inhibition for nanosuspension against coli (8.5±2.061 mm) and B. subtilus strains (8.25±2.031 mm) as compared to crude extract (4.5±1.5 mm) and (4±2 mm) respectively at 150 mg/mL. Optimized nanosuspension showed greater percentage antioxidant potential as compared to the crude extract.